Management of large class II lesions in molars: how to restore and when to perform surgical crown lengthening? - Ana Belén Dablanca-Blanco; Juan Blanco-Carrión; Benjamín Martín-Biedma; Purificación Varela-Patiño; Alba Bello-Castro; Pablo Castelo-Baz (Korean Academy of Conservative Dentistry, 2017)
The restoration of endodontic tooth is always a challenge for the clinician, not only due to excessive loss of tooth structure but also invasion of the biological width due to large decayed lesions. In this paper, the 7 most common clinical scenarios in molars with class II lesions ever deeper were examined. This includes both the type of restoration (direct or indirect) and the management of the cavity margin, such as the need for deep margin elevation (DME) or crown lengthening. It is necessary to have the DME when the healthy tooth remnant is in the sulcus or at the epithelium level. For caries that reaches the connective tissue or the bone crest, crown lengthening is required. Endocrowns are a good treatment option in the endodontically treated tooth when the loss of structure is advanced.